My Mind or Yours: Disorganised Attachment in Psychotherapy - Kanji, Ataya (Auckland University of Technology, 2023)
The current research explores the relational complexity of psychotherapeutic work with adult patients presenting with disorganised attachment. Where disorganised attachment patterns during infancy and childhood remain unresolved, sustained conflict at the level of the attachment system continues into adulthood. The emotional intimacy of being in a consistent therapeutic relationship often reactivates for the patient traumatic impressions of early pain, tumult, and terror. How can both parties in the therapeutic dyad live inside and live through the frightened, overwhelmed, dissociative, distrustful and non-relational aspects of the patient and their emotional self? Engaging in a hermeneutic literature review, I embrace the inherent contradictions and perplexities in the literature while listening to my subjective experience. I have applied clinical material, and my lived experience of disorganised attachment, to reflect on and analyse the strong transference/countertransference emotions and/or therapeutic dilemmas and enactments that characterise psychotherapy with disorganised attachment. What shines through is a discussion on questions of separateness and relatedness, and what happens in psychotherapy when the capacity for mutuality and intersubjectivity is limited or disturbed. The current research suggests that for patients to feel felt and for psychotherapy to progress, therapists must allow the unmanaged and unmanageable parts of the patient’s inner experience to exist within their mental field, which can evoke deep and complicated feelings of shame, powerlessness and helplessness. To be with patients and listen to them is to enter a new constellation of experience within the therapist’s self (Lewin & Schulz, 1992). Future research may re-examine the relational complexity of psychotherapy with disorganised attachment from cultural, socio-political, intersectional or systemic approaches.